Stewart‐Treves syndrome and other cutaneous malignancies in the context of chronic lymphedema: a systematic review. (1st July 2021) - Kim, Patrick J.; Mufti, Asfandyar; Sachdeva, Muskaan; Lytvyn, Yuliya; Zabihi‐Pour, Dorsa; Zaaroura, Hiba; Yeung, Jensen
Abstract: Introduction: Angiosarcoma developing in chronically lymphedematous tissue, or Stewart‐Treves syndrome (STS), is a rare and lethal complication of lymphedema. This systematic review summarizes characteristics and outcomes of STS and other cutaneous malignancies arising in chronic lymphedema. Methods: MEDLINE and EMBASE databases were searched on February 19th, 2021, to identify 200 articles included in the analysis. Results: Of 369 included patients, 89.7% ( n = 331/369) had STS and 10.3% ( n = 38/369) had other associated malignancies. Mean age of onset was 61.2 years, and 85.9% ( n = 317/369) of cases were female. Common risk factors were previous cancer history (69.8%, n = 258/369) and radiation history (53.7%, n = 198/369). Lymphedema was most commonly attributed to surgical causes (68.3%, n = 252/369). STS begins on average 14.9 years after lymphedema with mortality of 53.9% ( n = 178/331) and remission rate of 16.1% ( n = 53/331). Other malignancies begin on average 23.7 years after lymphedema, with mortality of 10.5% ( n = 4/38) and remission rate of 31.6% ( n = 12/38). STS and other malignancies had 5‐year survivals of 22.4% and 65.2%, respectively ( P = 0.00145). For all patients, patients initially treated with excision had the best survival (median: 48 months, 5‐year survival: 43.3%) and radiotherapy had the worst survival (median: 10 months, 5‐year survival: 6.5%) ( P = 0.0141). Conclusion: Malignancy can appear in lymphedematous tissue many years after lymphedema onset. STS has poorer prognosis compared to other malignancies. Further research should be conducted to better understand the causes, risk factors, and management of this phenomenon.